Revision of the Cleft Lip Nose - Angelos, Patrick; Wang, Tom (Facial Plastic Surgery, 2012)
Secondary or revision rhinoplasty for the cleft nasal deformity represents one of the most challenging problems in rhinoplasty surgery. The secondary nasal deformity of the unilateral cleft lip involves a retrodisplaced dome of the ipsilateral nasal tip, hooding of the alar rim, a secondary alar-columellar web, and other deficiencies. This article discusses techniques to achieve the best possible outcome for patients with cleft nasal deformities. We emphasize the importance of early intervention by way of primary cleft rhinoplasty and highlight the typical challenges presented in delayed (secondary) or revision cleft rhinoplasty. We describe how the sliding flap cheilorhinoplasty effectively corrects these deformities using a laterally based chondrocutaneous flap via an open rhinoplasty approach. Columellar struts and shield grafts are some of the techniques combined with this approach to produce optimal results.
Keywords: cleft; rhinoplasty; revision